Assessment of Serotonin Metabolite 5-hydroxyindoleacetic Acid Levels in Urine Sample for Diagnosis and Treatment Efficacy in Children with Dysfunctional Voiding and Their Interaction with Biofeedback Therapy - Bahadır Topuz; Giray Ergin; Burak Köprü; Turgay Ebiloğlu; Hasan Cem Irkılata; Yusuf Kibar; Musa Murat Dayanç (Journal of Urological Surgery, 2018)

(untitled)
Objective:Dysfunctional voiding (DV), which is explained as an incoordination between the external urethral sphincter and the bladder, is a situation developing in neurologically normal children. Serotonin has some effects on the lower urinary tract which cannot be fully explained. The selective 5-hydroxyindoleacetic acid (5-HIAA) agonist improves voiding efficacy in the rat model with voiding dysfunction as serotonin. Serotonin decomposes to 5-HIAA which excreted from urine. We considered that a problem in neuromodulator levels can lead to DV and evaluated the levels of 5-HIAA in urine.Materials and Methods:Our study included 130 children aged 5-15 years who were diagnosed with DV and 48 children with no urological complaints as controls. Urine samples were taken only once in control group, and 3 times [before and after the biofeedback treatment (sixth month and twelfth month)] in the study group to determine the difference and the interaction between 5-HIAA and biofeedback therapy.Results:Biofeedback therapy was found to be an effective method in the treatment of DV. However, there was no significant difference in the level of mean urine 5-HIAA/creatinine (u5-HIAA/Cr) between study (6.139±3.652) and control groups (6.374±4.329) (p=0.751). The mean u5-HIAA/Cr levels in the DV group at baseline and at the end of biofeedback therapy (6th month) were 6.249±4.132 and 6.19±4.715, respectively (p=0.951). The mean u5-HIAA/Cr levels in the DV group at baseline and at 12 months were 5.901±3.291 and 6.644±4.206, respectively (p=0.557). There was no significant difference in u5-HIAA/Cr levels between pre-treatment and post-treatment in the DV group.Conclusion:We still do not know if a problem at the level of neurotransmitter metabolite in the central nervous system plays a role in the etiology of DV. We evaluated this relationship, but we could not find a significant result. New studies are needed to get more information about the role of neuromodulators in the etiology and treatment of DV.